#ChalkedUnarmed. (17th September 2020) - NEZAM, MALLORY RUKHSANA
Abstract : Mall worker scrubbing off a #ChalkedUnarmed installation outside the Frontenac Mall, in a wealthy St. Louis suburb, May 2015. (Michael Kingsbaker)